Author Correction: Composition and Use of Cannabis Extracts for Childhood Epilepsy in the Australian Community - A. Suraev (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.